(3TQM cTa GdCSQGQs - (3fLe GdOjf YeQ Hf Ydj GdbRhjfi GdeTghQ HcGJHis; (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, CaVd GdOjf CHh YHO Gddg,J (B646 (3g` s
(3ChdgG (B:s
(3fSHM Gddg aGWQ PhGJ GdYbhd GdfhQjI aEf GdcJGH GdehShe HcTa GdGSQGQ ai GdefWb jTJed Ydi eHGMK TQjag s
(3BNQgG (B:s
(3HMSH GdhLhO GdNGQLi Cecf MjfFP dUOb bhdfG dGTF ef GdeeJO ai GdLgGJ Edi ZjQ GdfgGjI hGddg GYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1486s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs